2023
DOI: 10.1093/alcalc/agad015
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Alcohol Consumption in the General Population by Analysing Phosphatidylethanol Concentrations in Whole Blood: Results from 24,574 Subjects Included in the HUNT4 Study

Abstract: Aims To evaluate the association between self-reported alcohol consumption and phosphatidylethanol (PEth) concentrations in blood in a large general population study, and discuss optimal cut-off PEth concentrations for defined levels of alcohol consumption. Methods Population based, longitudinal cohort study including 24,574 adults from The Trøndelag Health Study 4 (HUNT4) conducted in Trøndelag County, Norway. Data included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
17
1
Order By: Relevance
“…The optimal PEth cutoff of 18.5 ng/mL is lower than cutoffs proposed based on comparisons with self-reported alcohol use in a population-based study in Norway, which found that 40 ng/mL was the optimal cutoff for detecting drinking more than 1 drink per day, which would meet criteria for heavy alcohol consumption in women, and 61 ng/mL for detecting drinking more than 2 drinks per day, which would meet criteria for heavy alcohol consumption for men . A likely explanation of the lower PEth cutoffs for heavy alcohol consumption in our study is that the mean age in our study was 66 years and all participants had a history of AF, compared with a mean age of 55 years in volunteers in the study conducted in Norway . While age was not associated with the sensitivity of PEth for unhealthy alcohol use in an individual-participant data meta-analysis (with median age of 38), a recent study that purposefully enrolled persons over age 60 years found that PEth values were negatively correlated with age …”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…The optimal PEth cutoff of 18.5 ng/mL is lower than cutoffs proposed based on comparisons with self-reported alcohol use in a population-based study in Norway, which found that 40 ng/mL was the optimal cutoff for detecting drinking more than 1 drink per day, which would meet criteria for heavy alcohol consumption in women, and 61 ng/mL for detecting drinking more than 2 drinks per day, which would meet criteria for heavy alcohol consumption for men . A likely explanation of the lower PEth cutoffs for heavy alcohol consumption in our study is that the mean age in our study was 66 years and all participants had a history of AF, compared with a mean age of 55 years in volunteers in the study conducted in Norway . While age was not associated with the sensitivity of PEth for unhealthy alcohol use in an individual-participant data meta-analysis (with median age of 38), a recent study that purposefully enrolled persons over age 60 years found that PEth values were negatively correlated with age …”
Section: Discussioncontrasting
confidence: 72%
“…21 A likely explanation of the lower PEth cutoffs for heavy alcohol consumption in our study is that the mean age in our study was 66 years and all participants had a history of AF, compared with a mean age of 55 years in volunteers in the study conducted in Norway. 21 While age was not associated with the sensitivity of PEth for unhealthy alcohol use in an individual-participant data meta-analysis (with median age of 38), 15 a recent study that purposefully enrolled persons over age 60 years found that PEth values were negatively correlated with age. 31 Our optimal cutoff was quite near the proposed consensus cutoff for general populations of 20 ng/mL for detecting alcohol use greater than low consumption or abstinence 32 ; this cutoff was also suggested in a review of the literature.…”
Section: Jama Network Open | Substance Use and Addictionmentioning
confidence: 54%
See 1 more Smart Citation
“…FibroScan was carried out using an M or XL probe (for patients with BMI ≥ 30 kg/m 2 ). All the enrolled subjects were given questionnaires that included questions about the frequency of any consumption of alcohol, the amount of alcohol usually consumed per week (specified as number of glasses or volumes of beer, wine, and liquor) and the frequency of binge drinking 22 . The level of alcohol intake was then quantified as 10–60 g/week 3 .…”
Section: Methodsmentioning
confidence: 99%
“…All the enrolled subjects were given questionnaires that included questions about the frequency of any consumption of alcohol, the amount of alcohol usually consumed per week (specified as number of glasses or volumes of beer, wine, and liquor) and the frequency of binge drinking. 22 The level of alcohol intake was then quantified as 10-60 g/week. 3 Longterm alcohol consumption was defined as >40 g alcohol consumption daily for women or >60 g alcohol consumption daily for men for ≥6 months.…”
Section: Patientsmentioning
confidence: 99%